A Tool to Measure Farmers’ Training Needs in Drone-based Technologies - B Arulmanikandan,; P. S. Shehrawat,; J S Malik,; Bhavesh,; Aditya, (Indian Journal of Extension Education, 2025)
A measurement tool has been developed to determine the training needs of farmers in the usage of drone-based technologies towards the sustainable agriculture. A list of 84 statements was collected and refined based on Edward’s 14 principles and 53 statements were retained for administering to farmers from non-sampling areas for further analysis. The statements were categorised under four constructs viz. Training Need for Drone Technical Knowledge (DTK), Platform for Learning Drone Technology (PLT), Practical Applications in Agriculture (TNP), Regulations, Permits, and Safety Protocols (TRS). Finally, the t-value for each statement was calculated and found that 34 statements hada t-value greater than 1.75. The 34 statements were further computed by item-total correlation analysis. The four items were found less than the threshold level of 0.30 implies a very weak association,and were removed to improve scale reliability. The final 30 statements were retained for the final scale and administered for reliability and validity testing. The Cronbach’s alpha coefficient validated that all four constructs demonstrated high reliability (α > 0.80), signifying that the items within each construct were strongly correlated and confirmed the internal consistency of the developed scale. The content validity of the scale was established with the judgement of the experts.